Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có:
\(\frac{1}{x-3}=\frac{2}{x}\)
\(\Rightarrow x=2\left(x-3\right)\)
\(\Rightarrow x=2x-6\)
\(\Rightarrow x=6\)
Vậy x = 6
( 5x - 24 ) : 73 = 27
=> 5x - 24 = 27 x 73
=> 5x - 24 = 9261
=> 5x = 9261 + 24
=> 5x = 9285
=> x = 9285 : 5
=> x = 1857
(5x – 24) . 73 = 2 . 74
(5x – 24) = 2. 74 : 73
(5x – 24) = 14
5x = 30
x = 6
\(\frac{2}{x}=\frac{y}{15}=\frac{\left(-25\right)}{75}\)
\(\Rightarrow\frac{y}{15}=\frac{\left(-1\right)}{3}\)
\(\frac{y}{15}=\frac{\left(-5\right)}{15}\)
\(\Rightarrow15y=15\times\left(-5\right)\)
\(15y=\left(-75\right)\)
\(y=\left(-75\right)\div15\)
\(y=\left(-5\right)\)
\(\Rightarrow\frac{2}{x}=\frac{\left(-5\right)}{15}\)
\(\frac{2}{x}=\frac{\left(-1\right)}{3}\)
\(\Rightarrow-x=3\times2\)
\(-x=6\)
\(x=\left(-6\right)\)
\(V\text{ậy}x=\left(-6\right);y=\left(-5\right)\)
Ư(6)={1;2;3;6}
Voi x +3=1=≫x=1-3=-2
Voi x+3=2=≫x=2-3=-1
Voi x+3=3=≫x=3-3=0
Voi x+3=6=≫x=6-3=3
Vi 10 la boi cua 2x+5=≫2x+5 la uoc cua 10=≫ Ư(10={1;2;5;10}
Voi 2x+5=1=≫2x=1-5=-4=≫x=4÷2=2
Voi 2x+5=2=≫ 2x=2-5=-3=≫x=-3÷2= -1,5
Voi 2x+5=5=≫5-5=0=≫x=0÷2=0
Voi 2x+5=10=≫2x=10-5=5=≫x=5÷2=2,5
(-5,6 ):3,5 = x : 25
=> x : 25 = -1,6
=> x = -1,6 x 25
Vậy x = -40
\(2\left(x-5\right)-17=25\)
\(2\left(x-5\right)=25+17\)
\(2\left(x-5\right)=42\)
\(x-5=42:2\)
\(x-5=21\)
\(x=21+5\)
\(x=26\)
Vậy x = 26
2(x - 5) - 17 = 25
2(x - 5) = 25 + 17
2(x - 5) = 42
x - 5 = 42 : 2
x - 5 = 21
x = 21
+ 5 = 26
x-25%x=1/2
1-3/4x=1/2
[1-3/4]x=1/2
1/4x=1/2
x=1/2:1/4
x=1/2.4/1
x=2
vậy x=2
chọn mình nha
1x - 3/4x = 1/2
( 1- 3/4 )x = 1/2
1/4x = 1/2
x = 1/2 : 1/4
x = 1/2 * 4/1
x = 2
Vậy x = 2